Determination of the causal relationship between beef prices and the consumer price index in Turkey - Akin, Ahmet Cumhur; Cevrimli, Mustafa Bahadir; Arikan, Mehmet Saltuk; Tekindal, Mustafa Agah (Tubitak Scientific & Technological Research Council Turkey, 2019)
The rising prices of beef meat have recently restricted its accessibility for consumers who need to consume it for a balanced and healthy diet. Speculations have been made about the increase in beef meat prices being one of the major factors underlying the increase in the consumer price index (CPI). In this scope, the causal relationship between the monthly average prices of beef and the rate of year-on-year change in the CPI for the period between January 2005 and February 2018 was analyzed in the study. Since time series data were used, the augmented Dickey-Fuller and Phillips-Perron tests were conducted to find out whether the series were stationary. Nonstationary series were made stationary by taking their difference. After conducting unit root test on the series, a vector auto regression model was developed, and the causality between the variables was tested by the Granger Causality Analysis. The results of the Granger Causality Analysis indicate that the monthly average price of beef and the rate of year-on-year change in the CPI are causally related at a level of 5% and 10%. In conclusion, the monthly data of the CPI and the beef prices between January 2005 and February 2018 are causally related at a significance level of 1%.
Keywords: Beef prices; causality; consumer price index; granger analysis; vector auto regression analysis